Toponymy Areas In Pesisir Selatan District: Analysis Anthropolinguistics - Aditiawarman, Mac; Sandari, Winda (Jurnal Ilmiah Pendidikan Scholastic, 2025)
The interest in conducting this research with the title Toponymy areas in Pesisir Selatan District: Analysis Anthropolinguistics. This research aims to analyze the toponymy or origin of regional names in Pesisir Selatan District and analyze the meaning and cultural elements of the region. The purpose of this anthropolinguistics study is to categorize and describe village toponymy, explain its cultural identification, and show the cultural values contained in the naming of regional names. The theories used in this research are anthropolinguistics, toponymy, sociolinguistics and semantics. This research is a field research using descriptive qualitative method. Data collection techniques in this research are using interview techniques, note-taking techniques, and recording techniques.Overall, regional toponymy in Pesisir Selatan District mostly consists of hydrological aspects and geomorphological aspects. This is motivated by the fact that the Pesisir Selatan District area was once a place that was mostly located on hydrology and the shape of the area in the area has become an icon and characteristic of the area. As for the history of the kingdom, it has existed since ancient times but did not last long because the average population in this area came from overseas who came from outside this District.